Effectiveness of Proanthocyanidin plus Trimetazidine in the Treatment of Non-Small-Cell Lung Cancer with Radiation Heart Injury. (3rd June 2022) - Yin, Hang; Zhao, Yue; Sun, Yucui; Liu, Jia; Han, Yingjun; Dai, Zhentao
Abstract : This study was intended to explore the effect of proanthocyanidin (PC) combined with trimetazidine in non-small-cell lung cancer (NSCLC) with radiation-induced heart damage (RIHD). It was a prospective randomized controlled study that 86 NSCLC patients with radiation treatment in Cangzhou People's Hospital from January 2019 and June 2021 were enrolled and randomized to either the control group or the study group via the random table method, 43 cases in each group. The control group received trimetazidine, and the study group additionally received PC. The incidence of RIHD-related clinical manifestation, RIHD-related ECG, and RIHD-related cardiac ultrasound change were all lower in the study group. After radiotherapy, the serum level of superoxide dismutase (SOD) was higher, and malondialdehyde (MDA) was lower in the study group when compared with the control group. After radiotherapy, the serum levels of brain natriuretic peptide (BNP), cardiac troponin (cTnT), creatine kinase (CK), and creatine kinase isoenzymes (CKMB) were all lower in the study group when compared with the control group. The efficacy of PC plus trimetazidine for NSCLC with RIHD is superior to trimetazidine alone, and it significantly mitigates radiation-induced inflammatory response and oxidative stress.